Regionalization methods for low flow estimation in ungauged catchments – a review - Agnieszka Cupak (Acta Scientiarum Polonorum. Formatio Circumiectus)
Aim of the study: The purpose of the paper is to look at the topic of estimation of the low flow characteristics at ungauged catchments in a balanced and systematic way, to provide a recent documentation of the subject and trace the most recent trends in low flow regionalization. The review focuses on methods, which are based on diverse methods that is the statistical, seasonal approach which are commonly used for the estimation of low flow characteristics in ungauged sites and which can be adopted in Polish conditions.